Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Leverage Terhadap Audit Delay (Studi Empiris Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia 2016-2021) - Endi Yana Saputra; Muhammad Fachruddin Arrozi (CV. Multi Kreasi Media, 2023)
This study aims to analyze the Effect of Company Size, Profitability, and Leverage on Audit Delays in Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 Period. Company size is proxied by ln total sales, profitability is measured by Return On Assets (ROA) measured by EBIT (Earning Before Interest and Tax) divided by total assets, leverage is measured by Debt To Equity Ratio where debt is divided by equity, and audit delay is measured by Audit report date divided by financial statement date. The method used is purposive sampling. The number of samples used in this study were 12 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. The type of data is secondary data sourced from financial reports and annual reports. The data analysis method used is multiple linear regression analysis. Hypothesis testing results indicate that simultaneous Company Size, Profitability, and Leverage significantly influence Audit Delay. Partially, company size do not have a significant effect on audit delays. While partially Profitability and Laverage has a significant effect on Audit Delay.